THE COMPOSITION OF SATURATED AND UNSATURATED FATTY ACIDS AND CHOLESTEROL IN MEAT OF BALI BULL FATTENED USING GREENLOT SYSTEM IN SMALL HOLDER FARMING - Tahuk, Paulus Klau; Dethan, Agustinus Agung; Sio, Stefanus (Universitas Syiah Kuala, 2018)
The objective of this research was to analyze the composition of saturated fatty acid, unsaturated fatty acids, and cholesterol in meat of Bali bull fattened using forage crops in small holder farming. The experiment was conducted for 3 months using nine Bali bull aged 2.5-3.5 years old with the initial body weight of 227-290 kg in the feedlots of Bero Sembada Farmers Group, Laen Manen Sub District, Malaka Regency, East Nusa Tenggara. The experiment was conducted based on the fattening system of local farmers in terms of feeding, housing, and health management. Feed given during the experiment was Centrosema pubences, Clitoria ternatea, fresh corn straw, king grass, Leucaena leucocepala, natural grass, Pennisteum purpureum, and Sesbania grandiflora. At the end of this study, cattle were slaughtered and the composition of saturated fatty acid, unsaturated fatty acids and cholesterol were measured. Data were analyzed using a descriptive statistic. Results revealed that the total of saturated fatty acid and unsaturated fatty acids in meat were 36.628% and 26.739%, respectively, while the cholesterol reached 79.18 mg/100 g of meat. In conclusion, meat of Bali bull fattened using forage crops in small holder farming has higher saturated fatty acid than unsaturated fatty acids.